The Impact of Economic and Political Transformation on the Polish Diaspora in Kazakhstan Since 1991 - Serebriansky, Yuriy (Institute of National Remembrance Review, 2025)
Following the collapse of the Soviet Union in 1991, the political and socio-economic landscape of the post-Soviet republics underwent significant transformation, opening new opportunities for their independent development and the assertion of national identity. At the same time, these newly independent states faced considerable economic challenges resulting from the disintegration of the centrally planned economy of the USSR, coupled with a lack of established external relations with other countries and international organisations. This article examines the impact of the political and economic changes in Kazakhstan since 1991 on the Polish diaspora as part of the country’s multiethnic population. The material analyzed in this study includes personal recollections of Poles published in the Ałmatyński Kurier Polonijny magazine between 2012 and 2017, as well as data from a survey conducted among Poles who emigrated from Kazakhstan to Poland for permanent residence since 2015, alongside responses from individuals currently residing in Kazakhstan.